2022
DOI: 10.1101/2022.12.05.22282985
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Longitudinal improvement in postural instability is distinct from gait in treated adult hydrocephalus

Abstract: Background: Ventriculoperitoneal shunting improves gait in patients with normal pressure hydrocephalus. Postural instability is a major concern, but mostly ignored in the evaluation and treatment of these patients. This study quantified postural instability using kinematics via a prospective cohort design. Methods: Seventeen patients with suspected normal pressure hydrocephalus and twenty age-matched, healthy controls underwent quantitative pull test and gait examinations while wearing inertial measurement uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“… 2 Given the primacy of gait and balance symptoms in NPH, a more quantitative method of assessment theoretically carries the benefit of being able to distinguish between the two diseases. In addition, postural instability in NPH improves with surgical treatment via VPS 13 while there are essentially no effective treatments for postural instability in PD. Previous work has demonstrated that the use of quantitative kinematics is helpful in examining gait and postural instability before and after surgery for patients with NPH and should be further investigated for patients with PD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 2 Given the primacy of gait and balance symptoms in NPH, a more quantitative method of assessment theoretically carries the benefit of being able to distinguish between the two diseases. In addition, postural instability in NPH improves with surgical treatment via VPS 13 while there are essentially no effective treatments for postural instability in PD. Previous work has demonstrated that the use of quantitative kinematics is helpful in examining gait and postural instability before and after surgery for patients with NPH and should be further investigated for patients with PD.…”
Section: Discussionmentioning
confidence: 99%
“…While these patient groups undergo different surgical intervention (VPS for NPH and DBS for PD), the overall goal of surgical intervention improving postural instability remains the same and an important next step to investigate. 13 Quantitative methods allow for the possibility of detailing small changes in the postural response when assessing new treatments or understanding the pathophysiology of postural instability. Canonically, ordinal rating scales have been used in the clinical assessment of these patients, but with the limitations of between- and within-provider variability and subjectivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation